Escape expectancies and sexualized substance use among gay, bisexual, and other men who have sex with men. Issue 12 (1st December 2020) - Card, Kiffer G.; Armstrong, Heather L.; Wang, Lu; Bacani, Nicanor; Moore, David M.; Roth, Eric A.; Hogg, Robert S.; Lachowsky, Nathan J.
ABSTRACT: McKirnan's Cognitive Escape Theory (1996) is often characterized by the hypothesis that drugs are used during sex by gay, bisexual, and other men who have sex with men (gbMSM) to relieve internal cognitive conflict over safe-sex norms and sexual desire. We examined how McKirnan's Cognitive Escape Scale (CES) is related to other widely used constructs relevant to sexualized substance use with hopes of better situating the theory within the evolving landscape of HIV-prevention. Associations between CES and trait anxiety, depression, treatment optimism, sexual altruism, sexual sensation seeking, and self-perceived risk for HIV transmission/acquisition were tested. Mediation analyses tested whether associated psychological measures mediated the effect of CES on the proportion of events in which participants reported co-occurrent substance use and condomless anal sex. Results indicated that CES is associated with higher sexual sensation seeking, treatment optimism, trait anxiety, and perceived likelihood of HIV transmission/acquisition. Mediation analyses suggest that CES is related to but operates independently of treatment optimism, sensation seeking, and trait anxiety. Nevertheless, the intersection of HIV-related worries and substance use expectancies are clearly more nuanced than is widely reported is discussions on cognitive escape.